Settlement of Disputes over Rice Field Land Ownership Rights Due to Unauthorized buying and selling - Wahyu Prawesthi; Mohammad Dwi Febriyanto; Fajar Rachmad Dwi Miarsa (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2023)
Rice field land is a general term such as forest land, plantation land and so on. All kinds of soil can be cultivated as long as it has sufficient water availability. Problems with land are quite serious. So that handling must also be done seriously. Both through prefective means, namely by providing understanding by related devices or institutions and by repressive means or resolution due to disputes. In this way, it is hoped that the community can understand the validity of buying and selling land and its settlement. So that rice field land disputes due to buying and selling do not have an impact on agricultural activities. This study uses a type of normative juridical legal research, namely legal research conducted by examining primary legal materials in the form of laws and regulations and secondary legal materials or legal materials in the form of supporting library materials for primary legal materials. The buying and selling process is legally valid if material conditions are met. In relation to the rules governing the authority and competence of the parties, as well as the fulfillment of conditions by the buyer to become the holder of the right to the purchased land. The validity of buying and selling paddy fields is the same as buying and selling land in general. The sale and purchase of paddy fields is canceled if it can cause a reduction in the minimum limit of agricultural land ownership. Dispute resolution can be done through litigation and non-litigation resolution. The advantage obtained when using litigation settlement is that it has definite legal force and is final.